Maximal bewegliche Hyperflächenelementenräume mit einem allgemeinen affinen Zusammenhang - Urbonas, A. (Lithuanian Mathematical Journal, 1969)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: А. П. Урбонас. Максимально подвижные пространства гиперплоскостных элементов общей аффинной связности A. Urbonas. Maksimaliai judrios hiperplokštuminių elementų erdvės su bendru afininiu sąryšiu